Efficient anti-bioadhesion silicone rubber coating with dynamic surface structure as well as preparation and application of efficient anti-bioadhesion silicone rubber coating

By modifying polyroxane on the surface of silicone rubber and using its molecular motion ability to form a silicone rubber coating with a dynamic surface structure, the problem that silicone rubber implanted materials are easily adhered to biological substances after long-term implantation is solved, achieving efficient anti-bioadhesion effect and reducing the risk of infection.

CN119701106APending Publication Date: 2025-03-28THE FIRST AFFILIATED HOSPITAL OF JINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411814627.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing silicone rubber implant materials are easily adhered to proteins, bacteria and tissue fluid after long-term implantation, resulting in an increase in the risk of biological contamination and infection, especially in equipment such as urinary catheters, which can easily cause problems such as catheter blockage and leakage.

Method used

By modifying polyroxane to the silicone rubber surface of the polydopamine-coated silicone rubber surface, the molecular motility of the zwitterionic betaine modified on the polyroxane is used to form a highly efficient anti-bioadhesive silicone rubber coating with a dynamic surface structure.

Benefits of technology

The space utilization rate of zwitterion is significantly improved, efficient physical anti-bioadhesion is achieved, and bacterial adhesion, protein crystallization and biofilm formation is reduced, reducing the risk of infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701106A_ABST
    Figure CN119701106A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient anti-bioadhesion silicone rubber coating with a dynamic surface structure as well as preparation and application of the efficient anti-bioadhesion silicone rubber coating. According to the invention, polyrotaxane is modified on the silicone rubber surface of a polydopamine coating, and the space utilization rate of zwitter-ions is improved by utilizing the molecular movement capability of cyclodextrin modified by zwitter-ion betaine on polyrotaxane, so that bacterial adhesion, protein crystallization and biofilm formation can be effectively reduced or prevented; potential biotoxicity and adverse reactions caused by loading of antibiotic drugs or other metal ions are avoided; the silicon rubber implant is used for solving the clinical biological infection and complications caused by retention of the silicon rubber implant. The coating material disclosed by the invention has more modification sites, other ligands or drugs can be modified or loaded on the surface structure of the coating so as to meet complicated and changeable clinical requirements, and the application in the aspect of in-vitro biological detection can also be expanded; the preparation operation is simple, no complex chemical modification process exists, the related composition structure is clear, and the clinical application is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical implant materials, and particularly relates to a highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure and the preparation and application thereof. Background Art

[0002] Silicone rubber implant materials can meet diverse clinical needs due to their unique physical and chemical properties and processing performance. They are widely used in many fields including cochlear implants, catheters, heart valves, breast implants, ophthalmic implants and wound dressings. Although silicone rubber materials have shown many advantages in the medical field, there are still some shortcomings in their application. Especially in the case of long-term implantation, the surface of silicone rubber is easily adhered by proteins, bacteria and tissue fluid, leading to biological contamination and increased risk of infection. For various catheters commonly used in urology, such as catheters, ureteral stents, and nephrostomy catheters, patients who use them continuously for many days often encounter problems such as catheter blockage and leakage due to the presence of multiple biological adhesions, causing catheter-related urinary tract infections, which significantly increases the risk of patients acquiring bacteremia and greatly increases the morbidity and mortality of postoperative infections.

[0003] With the continuous development of silicone rubber implant materials and coating technology, a large number of researchers have developed a variety of treatment strategies to solve the problem of anti-biological adhesion of silicone rubber implant materials and the related complications induced by them. Among different types of functional coatings, biopolymer coatings have shown outstanding potential in various biomedical applications due to their flexible functional properties. Belfield et al. prepared a polymer antibacterial catheter that simultaneously carried rifampicin, triclosan and sparfloxacin. The study found that the coated catheter can inhibit the growth of a variety of bacteria (Acta Biomaterialia, 2019, 90: 157-68.). Metal ions are also widely used in antibacterial coatings. For example, silver is the preferred coating for hemodialysis catheters. It can prevent the formation of biofilm on the catheter surface and the replication of bacterial DNA, thereby effectively inhibiting the reproduction of bacteria and fungi (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2021, 109 (3): 314-327.). The team of the inventor used zwitterion-modified dopamine molecules to polymerize the silicone surface, which significantly improved the hydrophilicity of the cochlear implant surface and effectively reduced the adhesion of macrophages, thereby improving the inflammatory response after silicone rubber implantation to a certain extent (Advanced Healthcare Materials, 2023, 12(1): 2200807.).

[0004] Although the coating modification technology of silicone rubber implant materials has been developed for many years, whether it is a polymer coating loaded with antibiotics, an anti-bioadhesion coating loaded with metal ions, or a single hydrophilic-hydrophobic modified polymer coating, there are a lot of uncertainties in its performance and biosafety, and traditional polymer coatings cannot match the complex and changeable dynamic microenvironment in the body. Therefore, the development of silicone rubber implant materials with long-term anti-bioadhesion properties has become an important issue that needs to be solved urgently.

[0005] Polyrotaxane is a molecular collection composed of multiple ring molecules and a chain molecule. The chain molecule acts as an axis to pass through the cavity of the ring. Both ends of the chain molecule are capped with larger molecules to prevent the ring from sliding out, thus forming a rotaxane structure with unique molecular motion characteristics. The uniqueness of the polyrotaxane structure lies in that its main molecule cyclodextrin can slide and rotate on the polymer chain, thus giving the material the special property of dynamic reversibility. Currently, the most common type is cyclodextrin polyrotaxane, which is a polyrotaxane structure material formed by α-cyclodextrin (α-CD) as the main molecule and the polymer chain through host-guest interaction. It has attracted widespread attention in the field of biomedical engineering because of its flexible molecular motion, multiple modifiable sites (a large number of hydroxyl groups), low cost, and good biocompatibility.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure. Specifically, polyrotaxane is modified on the silicone rubber surface of the polydopamine coating, and the molecular mobility of the zwitterionic betaine-modified cyclodextrin on the polyrotaxane is utilized to overcome the problems of steric hindrance, uneven distribution, and weak action force existing in ordinary anti-adhesion coating materials, thereby improving the spatial utilization rate of zwitterions and achieving the purpose of highly efficient physical anti-biological adhesion; and related silicone rubber surface modification technologies derived from this concept are used to solve the biological infection and complications caused by retained silicone rubber implants in clinical practice.

[0008] Another object of the present invention is to provide a highly efficient anti-biological adhesion silicone rubber coating having a dynamic surface structure prepared by the above preparation method.

[0009] Another object of the present invention is to provide the application of the above-mentioned highly efficient anti-biological adhesion silicone rubber coating with dynamic surface structure.

[0010] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure comprises the following steps: Multiple host molecules α-cyclodextrin (α-CD) and guest molecules double-terminated amino polyethylene glycol (NH2-PEG-NH2) were assembled to form pseudopolyrotaxane (PPR), which was capped with a polydopamine (PDA) coating to obtain a polyrotaxane (PR) structure with molecular mobility. The coating surface was further modified with zwitterionic betaine (such as SBMA) to prepare a highly efficient anti-bioadhesion silicone rubber coating (such as PDA@PR@SBMA) with a dynamic surface structure. The synthetic route is as follows: Figure 7 shown.

[0011] The method for preparing the above-mentioned highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure specifically comprises the following steps: (1) Synthesis of pseudopolyrotaxane (PPR) Take double-terminal amino polyethylene glycol NH2-PEG-NH2 and dissolve it in pure water, add a certain amount of α-CD, and stabilize it with ultrasound until it becomes a uniform milky white colloid, and continue to stir at room temperature; the product is washed by centrifugation with pure water and freeze-dried to obtain pseudopolyrotaxane PPR; (2) Synthesis of polyrotaxane coating (PDA@PR) The pseudopolyrotaxane PPR obtained in step (1) is modified onto a polydopamine silicone rubber sheet to obtain a polyrotaxane coating (PDA@PR); the polydopamine silicone rubber sheet is a silicone rubber sheet wrapped with a PDA coating.

[0012] (3) Synthesis of zwitterion-modified polyrotaxane coatings The polyrotaxane coating (PDA@PR) obtained in step (2) is modified with zwitterionic betaine to obtain a zwitterionic modified polyrotaxane coating, i.e., a silicone rubber coating with a dynamic surface structure and high efficiency in anti-bioadhesion.

[0013] In step (1), The mass ratio of the double-terminated amino polyethylene glycol NH2-PEG-NH2 to α-CD is 1:1-3 (preferably 1:1.5); the amount of the double-terminated amino polyethylene glycol NH2-PEG-NH2 is calculated by adding 1-2 g per 10 mL of pure water; The molecular weight of the polyethylene glycol in the double-terminated amino polyethylene glycol NH2-PEG-NH2 is 3000 to 12000; In some embodiments, the molecular weight of the polyethylene glycol in the double-terminal amino polyethylene glycol NH2-PEG-NH2 is 6,000.

[0014] The ultrasonic stabilization time is 5 to 15 minutes; the ultrasonic power is 200 to 700 W, further 500 W; The stirring time is 6 to 18 h; further 12 h.

[0015] The number of centrifugal washing is 3 to 4 times.

[0016] The rotation speed of the centrifugal washing is 4000-8000 rpm, and the centrifugal time for each time is 20-50 min; further, the rotation speed is 5000 rpm, and the centrifugal time for each time is 30 min.

[0017] Preferably, in step (1), the preparation method of the double-terminated amino polyethylene glycol NH2-PEG-NH2 comprises the following steps: dissolving polyethylene glycol PEG in anhydrous N,N-dimethylformamide (DMF), adding N,N′-carbonyldiimidazole (CDI) and triethylamine, reacting at room temperature to obtain a mixed solution; dissolving ethylenediamine in anhydrous DMF, adding triethylamine, and then slowly adding the above mixed solution; reacting at room temperature, quenching the reaction, extracting the obtained product, and finally removing water, rotary evaporating to obtain the product double-terminated amino polyethylene glycol NH2-PEG-NH2.

[0018] Preferably, the molecular weight of the polyethylene glycol PEG is 3000-12000; in some embodiments, the molecular weight of the polyethylene glycol PEG is 6000.

[0019] Preferably, the mass ratio of the CDI, PEG and ethylenediamine is 1:2-4:2-4, further 1:2:2; the amount of the triethylamine is 30-70 μL (preferably 50 μL) added to every 10 mL of anhydrous DMF; the amount of the PEG is 1-3 g (preferably 1.7 g) added to every 10 mL of anhydrous DMF.

[0020] Preferably, the reaction time at room temperature is 1 to 5 h; further preferably 3 h.

[0021] Preferably, the slow adding time is 1 to 5 h; further preferably 3 h.

[0022] Preferably, the reaction time at room temperature is 12 to 15 h; further preferably 12 h.

[0023] Preferably, the quenching reaction is performed by adding dichloromethane to quench the reaction.

[0024] Preferably, the extraction is performed by sequentially adding saturated sodium bicarbonate and sodium chloride aqueous solutions for layered extraction.

[0025] Preferably, the dehydration is performed by adding anhydrous sodium sulfate.

[0026] The step (2) specifically comprises the following steps: soaking the polydopamine silicone rubber sheet in a Tris-HCl buffer, adding the pseudopolyrotaxane PPR obtained in the step (1), and stirring the reaction under normal temperature and pressure to obtain a polyrotaxane coating (PDA@PR).

[0027] Preferably, the molar concentration of the Tris-HCl buffer is 1-3 M; further preferably 2 M.

[0028] Preferably, the amount of the pseudopolyrotaxane PPR is 10-20 mg per 10 mL Tris-HCl buffer; the amount of the Tris-HCl buffer is per 25π mm 3 The silicone rubber sheet is calculated using 4 to 8 mL (further calculated as 5 mL); Preferably, the stirring reaction time is 12 to 36 h; further preferably 24 h.

[0029] In step (2), the method for preparing the polydopamine silicone rubber sheet comprises the following steps: treating the surface of the silicone rubber sheet, then immersing it in anhydrous ethanol and ultrasonically treating it; after drying, immersing it in a Tris-HCl buffer solution containing dopamine hydrochloride, reacting it, washing it and drying it to obtain a silicone rubber sheet wrapped with a PDA coating, namely, a polydopamine silicone rubber sheet.

[0030] Preferably, the molar concentration of the Tris-HCl buffer is 5 to 10 mM; the amount of dopamine hydrochloride is calculated by adding 0.1 to 0.2 g per 10 mL Tris-HCl buffer; the amount of anhydrous ethanol and Tris-HCl buffer is calculated by adding 0.1 to 0.2 g per 25 mM Tris-HCl buffer. 3 The silicone rubber sheet is calculated using 4 to 8 mL (further calculated as 5 mL); Preferably, the surface treatment of the silicone rubber sheet is to treat the surface of the silicone rubber sheet with a plasma cleaning agent under normal pressure; Preferably, the surface treatment time is 1 to 5 min; further preferably 3 min.

[0031] Preferably, the ultrasonic treatment time is 1 to 3 h; the ultrasonic power is 200 to 700 W, further 500 W; Preferably, the reaction is carried out at 60-80° C. for 6-18 h; further at 80° C. for 12 h.

[0032] Preferably, the washing is performed using deionized water; and the drying is performed using nitrogen gas.

[0033] In step (3), the zwitterionic betaine is methyl methacryloylethyl sulfobetaine (SBMA), but is not limited thereto.

[0034] The step (3) specifically comprises the following steps: placing the polyrotaxane coating (PDA@PR) obtained in step (2) in anhydrous DMF, then adding CDI, reacting, washing with anhydrous DMF, placing it in anhydrous DMF again, then adding diaminobutane, continuing the reaction, and alternately washing the silicone rubber sheet with DMF and pure water to obtain a modified silicone rubber sheet; placing the modified silicone rubber sheet in anhydrous methanol solution of zwitterionic betaine, and continuing the reaction to obtain a zwitterionic modified polyrotaxane coating, that is, a silicone rubber coating with a dynamic surface structure and high efficiency and anti-bioadhesion.

[0035] Preferably, the amount of CDI is calculated by adding 50 to 200 mg (preferably 100 mg) per 5 mL of anhydrous DMF; the amount of anhydrous DMF is calculated by adding 50 to 200 mg (preferably 100 mg) per 25 mm 3 The amount of silicone rubber sheet is calculated by adding 5 to 15 mL (further 10 mL); the amount of diaminodiphenylamine is calculated by adding 100 to 400 mg (preferably 200 mg) to every 5 mL of anhydrous DMF; the amount of zwitterionic betaine is calculated by adding 0.5 to 2.5 g (preferably 1.5 g) to every 10 mL of anhydrous methanol; the amount of anhydrous methanol is calculated by adding 25π mm 3 The silicone rubber sheet is calculated using 5 to 15 mL (further calculated as 10 mL); Preferably, the reaction time is 3 to 12 h; further preferably 12 h.

[0036] Preferably, the washing with anhydrous DMF is washing with anhydrous DMF for 1 to 3 times (preferably 2 times).

[0037] Preferably, the continued reaction time is 6 to 18 h; further 12 h.

[0038] Preferably, the sustained reaction time is 24 to 48 h; further preferably 24 h.

[0039] In the present invention, the room temperature or normal temperature is 5 to 35°C; further 15 to 35°C.

[0040] In the present invention, the preparation method of anhydrous N,N-dimethylformamide (DMF) is according to the following operating steps: adding calcium hydride to DMF, stirring for 6 to 24 hours, and then distilling under reduced pressure to obtain anhydrous DMF, wherein the amount of calcium hydride added is 1 to 2 g per 500 mL of N,N-dimethylformamide.

[0041] In the present invention, the preparation method of anhydrous methanol follows the following operating steps: adding calcium hydride to methanol, stirring for 6 to 24 hours, and distilling at atmospheric pressure to obtain anhydrous methanol, wherein the amount of calcium hydride added is 1 to 2 g per 500 mL of methanol.

[0042] A highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure is prepared by the preparation method.

[0043] Application of the highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure in highly efficient anti-biological adhesion; Preferably, the anti-biological adhesion comprises at least one of anti-bacterial adhesion, anti-bacterial biofilm adhesion and anti-protein adhesion.

[0044] More preferably, the bacteria include Escherichia coli and the like.

[0045] The application of the highly efficient anti-bioadhesion silicone rubber coating with a dynamic surface structure in the field of biomedical engineering is further applied in the preparation of retention silicone rubber implants.

[0046] The above-mentioned highly efficient anti-bioadhesion silicone rubber coating with dynamic surface structure (such as PDA@PR@SBMA) can provide a new solution for the treatment of clinical diseases such as biological infections and complications caused by retained silicone rubber implants.

[0047] Compared with the prior art, the present invention has the following advantages and effects: (1) The present invention uses a polyrotaxane structure with flexible molecular mobility as the surface modification polymer of the silicone rubber implant. Compared with the zwitterionic surface coating material with fixed spatial position, the flexible and movable characteristics of the polyrotaxane structure greatly improve the spatial utilization rate of the zwitterions, which can effectively reduce or prevent bacterial adhesion, protein crystallization and biofilm formation.

[0048] (2) The coating material with dynamic motion structural characteristics designed by the present invention realizes anti-biological adhesion only through the physical structure of the silicone rubber surface, and achieves the effect of reducing or preventing protein crystallization and biofilm formation, avoiding the potential biological toxicity and adverse reactions caused by loading antibiotics or other metal ions.

[0049] (3) The highly efficient anti-bioadhesion silicone rubber coating with a dynamic surface structure (such as the PDA@PR@SBMA coating) of the present invention is easy to prepare, does not involve a complicated chemical modification process, has a clear composition structure, and is widely used in clinical practice.

[0050] (4) The coating material with dynamic motion structural characteristics of the present invention has a large number of modification sites, which can be used to modify or load other ligands or drugs on the coating surface structure to meet complex and changing clinical needs, and can also expand its application in in vitro biological detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1Near-infrared spectrum of silicone rubber surface material during the preparation of PDA@PR@SBMA, a silicone rubber coating with a dynamic surface structure and high efficiency against bioadhesion.

[0052] Figure 2 This is a diagram showing the structural morphology changes on the silicone rubber surface during the preparation of PDA@PR@SBMA, a silicone rubber coating with a dynamic surface structure and high efficiency in anti-bioadhesion.

[0053] Figure 3 Biosafety evaluation of PDA@PR@SBMA, a highly efficient anti-bioadhesion silicone rubber coating with a dynamic surface structure: NIH / 3T3 cells were used to determine the cell survival rate under the action of PDA@PR@SBMA and control group materials.

[0054] Figure 4 In vitro evaluation of the antibacterial adhesion properties of PDA@PR@SBMA, a silicone rubber coating with a dynamic surface structure, for efficient anti-bioadhesion: using E. coli The number of bacteria adhering to the surface of the materials after incubation with each group of materials for 24 h.

[0055] Figure 5 Evaluation of the in vitro antibacterial biofilm adhesion properties of PDA@PR@SBMA, a silicone rubber coating with a dynamic surface structure, for efficient anti-bioadhesion: using E. coli Investigate the biofilm formation on the surface of each group of materials.

[0056] Figure 6 Evaluation of the in vitro anti-protein adhesion performance of PDA@PR@SBMA, a silicone rubber coating with a dynamic surface structure and high efficiency anti-bioadhesion: Fluorescently labeled bovine serum albumin was used to investigate the surface protein adhesion of each group of materials.

[0057] Figure 7 This is a synthetic route for the highly efficient anti-bioadhesion silicone rubber coating PDA@PR@SBMA material with a dynamic surface structure of the present invention. DETAILED DESCRIPTION

[0058] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The experimental methods in the following examples where specific experimental conditions are not specified are usually carried out under conventional experimental conditions or according to the experimental conditions recommended by the manufacturer. The materials, reagents, etc. used are reagents and materials obtained from commercial sources unless otherwise specified.

[0059] The preparation method of anhydrous N,N-dimethylformamide (DMF) described in the following examples is as follows: adding calcium hydride to DMF, stirring for 12 h, and then distilling under reduced pressure to obtain anhydrous DMF, wherein the amount of calcium hydride added is 2 g per 500 mL of N,N-dimethylformamide; The preparation method of anhydrous methanol described in the following example follows the following operating steps: adding calcium hydride to methanol, stirring for 12 hours, and then distilling at atmospheric pressure to obtain anhydrous methanol, wherein the amount of calcium hydride added is 2 g per 500 mL of methanol.

[0060] Example 1: Synthesis of polydopamine silicone rubber sheet (PDA silicone rubber sheet) Take the silicone rubber sheet and cut it into uniformly sized discs with a diameter of 1 cm (volume 25π mm 3 ), the surface was modified with PDA coating. The surface of the silicone rubber sheet was treated with a plasma cleaner for 3 min at normal pressure, and then immersed in anhydrous ethanol and ultrasonically treated for 1 h. After drying, it was immersed in a Tris-HCl buffer (pH = 8.5) containing a certain amount of dopamine hydrochloride, reacted at 80°C for 12 h, washed with deionized water and dried with nitrogen to obtain a material wrapped with a PDA coating, namely a PDA silicone rubber sheet. The power of the ultrasound was 500 W; the molar concentration of the Tris-HCl buffer was 5 mM; the amount of dopamine hydrochloride was calculated by adding 0.1 g to every 10 mL of Tris-HCl buffer; the amounts of anhydrous ethanol and Tris-HCl buffer were both calculated by adding 0.1 g to every 25π mm 3 The silicone rubber sheet is calculated using 5 mL.

[0061] Example 2: Synthesis of double-terminated amino polyethylene glycol (NH2-PEG-NH2) A certain molecular weight of polyethylene glycol PEG is dissolved in anhydrous N,N-dimethylformamide (DMF), a certain amount of N,N′-carbonyldiimidazole (CDI) and triethylamine are added, and the mixture is reacted at room temperature of 35°C for 3 h under certain conditions to obtain a mixed solution. A certain amount of ethylenediamine is dissolved in anhydrous DMF, triethylamine is added, and then the above mixed solution is slowly added within 3 h; under certain conditions, dichloromethane is added to quench the reaction after reacting at 35°C for 12 h, and the obtained product is sequentially added with saturated sodium bicarbonate and sodium chloride aqueous solutions for layered extraction, and finally anhydrous sodium sulfate is added to remove water, and the product NH2-PEG-NH2 is obtained by rotary evaporation. The molecular weight of the polyethylene glycol PEG is 6000. The mass ratio of the CDI, PEG and ethylenediamine is 1:2:2; the amount of triethylamine is 50 μL per 10 mL of anhydrous DMF; the amount of PEG is 1.7 g per 10 mL of anhydrous DMF.

[0062] Example 3: Synthesis of Pseudopolyrotaxane (PPR) Take a certain amount of NH2-PEG-NH2 obtained in Example 2 and dissolve it in pure water, add a certain amount of α-cyclodextrin (α-CD), and stabilize it with ultrasound for 15 min until it becomes a uniform milky white colloid, and continue stirring at room temperature for 12 h. The product is washed by centrifugation with pure water, and the operation is repeated 3 times, and freeze-dried to obtain pseudopolyrotaxane PPR. The mass ratio of NH2-PEG-NH2 to α-CD is 1:1.5; the amount of NH2-PEG-NH2 is calculated by adding 1 g of NH2-PEG-NH2 to every 10 mL of pure water; the power of the ultrasound is 500W; the speed of the centrifugal washing is 5000 rpm, and the centrifugal time for each time is 30 min.

[0063] Example 4: Synthesis of polyrotaxane coating (PDA@PR) In order to construct a silicone coating with a dynamic surface structure, the PPR obtained in Example 3 was modified onto the polydopamine silicone rubber sheet obtained in Example 1. The PDA silicone rubber sheet obtained in Example 1 was soaked in a certain amount of Tris-HCl buffer, and a certain amount of PPR obtained in Example 3 was added. The reaction was stirred for 24 hours at room temperature and pressure to complete the end-capping and obtain the polyrotaxane coating PDA@PR. The molar concentration of the Tris-HCl buffer was 2 M; the amount of the PPR was 10 mg per 10 mL of Tris-HCl buffer; the amount of the Tris-HCl buffer was per 25π mm 3 The silicone rubber sheet is calculated using 5 mL.

[0064] Example 5: Synthesis of zwitterionic betaine-modified polyrotaxane coating (PDA@PR@SBMA) The polyrotaxane coating PDA@PR obtained in Example 4 (i.e., the silicone rubber sheet modified with the polyrotaxane coating PDA@PR) was placed in anhydrous DMF, and then a certain amount of CDI was added. After reacting for 12 h, the silicone rubber sheet was washed twice with anhydrous DMF, and then placed in anhydrous DMF again, and then a certain amount of diaminodiphenylamine was added. The reaction was continued for 12 h, and the silicone rubber sheet was rinsed alternately with DMF and pure water to obtain a modified silicone rubber sheet. Further, the modified silicone rubber sheet was placed in a certain amount of anhydrous methanol solution of methyl methacryloylethyl sulfobetaine (SBMA), and the reaction was continued for 24 h to finally obtain a silicone rubber coating (PDA@PR@SBMA) with a dynamic surface structure. The synthesis route is as follows: Figure 7 The amount of CDI is calculated by adding 100 mg to every 5 mL of anhydrous DMF; the amount of anhydrous DMF is calculated by adding 100 mg to every 25 mm 3The amount of silicone rubber sheet is calculated by adding 10 mL; the amount of diaminodiphenylamine is calculated by adding 200 mg per 5 mL of anhydrous DMF; the amount of methacryloylethyl sulfobetaine is calculated by adding 1.5 g per 10 mL of anhydrous methanol; the amount of anhydrous methanol is calculated by adding 1.5 g per 25π mm 3 The silicone rubber sheet is calculated using 10 mL.

[0065] Example 6: Synthesis of zwitterionic betaine-modified polydopamine (PDA@SBMA) The silicone coating without a dynamic surface structure was used as the control group, that is, the zwitterionic betaine SBMA was directly modified onto the polydopamine silicone rubber sheet obtained in Example 1 to obtain a PDA@SBMA coating. The specific experimental steps are as follows: first, the PDA silicone rubber sheet obtained in Example 1 was immersed in 5 mL of 1 M Tris-HCl buffer, and dibutyl amine was added at the same time. The reaction was stirred for 24 hours at room temperature and pressure. After washing with pure water three times, SBMA was added and reacted in 10 mL of anhydrous methanol for 24 hours to obtain PDA@SBMA. The amount of dibutyl amine used was calculated by adding 200 mg per 5 mL of Tris-HCl buffer; the amount of SBMA used was calculated by adding 2 g per 10 mL of anhydrous methanol; the amount of anhydrous methanol used was calculated by adding 2 g per 25π mm 3 The silicone rubber sheet is calculated using 10 mL.

[0066] Example 7 The PDA silicone rubber sheet obtained in Example 1, the PDA@PR@SBMA obtained in Example 5, and the PDA@SBMA obtained in Example 6 were characterized by infrared spectroscopy using the potassium bromide tableting method. The results are shown in FIG. Figure 1 As shown, the polydopamine silicone rubber sheet is at 1000 cm -1 ~1500 cm -1 There are obvious COC skeleton vibration peaks and CH in-plane bending vibration peaks at 1640 cm-1, which are the same as the near-infrared characteristic peaks of PDA, indicating that the silicone rubber surface has been successfully modified with PDA coating; PDA@SBMA has a peak at 1640 cm-1. -1 and 1550 cm -1 The obvious carbonyl stretching vibration peak and alkyl deformation vibration peak are the infrared absorption peaks unique to SBMA (black dashed box), indicating that SBMA has been successfully grafted onto the surface of the PDA coating. Furthermore, we performed near-infrared measurement on PDA@PR@SBMA, which was modified with polyrotaxane and then further modified with SBMA, and found that at 1545 cm -1 The stretching vibration peaks of the alcohol hydroxyl carbon and oxygen on α-cyclodextrin in PR and CO appeared at 2940 cm -1 and 2840 cm -1The absorption peaks of -CH2- asymmetric stretching vibration and symmetric stretching vibration on PEG in PR are shown in Figure 2. Therefore, this result fully proves that the surface of silicone rubber has been fully modified by polyrotaxane PR, and the PDA@PR@SBMA coating structure has been successfully prepared.

[0067] Example 8 A blank silicone rubber sheet (Uncoated), the materials obtained in Example 1, Example 5, and Example 6 were placed on a scanning electron microscope stand, gold plated, and sprayed onto a copper mesh to observe the surface morphology changes of the materials with different coatings. The results are as follows: Figure 2 As shown in the figure, compared with the silicone rubber surface without any modification, the surface roughness and granular layer of the silicone rubber modified by PDA are more obvious; the successful grafting of SBMA did not significantly change the surface morphology of the PDA coating, so the morphology of the PDA@SBMA coating still maintained obvious roughness and granularity; further, the morphological characteristics of PDA@PR@SBMA were observed by SEM, and it was found that its surface roughness was low and regular and smooth. This is because a large number of polyrotaxane structures are formed on the surface of silicone rubber, and α-cyclodextrin is stacked and arranged to form a transistor-like structure, resulting in an orderly arrangement of the surface. This also fully proves that the polyrotaxane structure is successfully modified on the silicone rubber surface and the PDA@PR@SBMA coating structure is successfully prepared.

[0068] Example 9 In order to explore and evaluate the biosafety of each material in the preparation process of PDA@PR@SBMA, an in vitro cytotoxicity experiment was conducted. The specific steps are as follows: take a piece of coating material obtained in Example 1, Example 5, and Example 6 with a diameter of 1 cm, place it in 10 mL PBS solution and incubate it at 37 °C for 3 days, then filter the leaching solution through a 0.22 μm filter membrane to obtain the material leaching solution; NIH / 3T3 (mouse embryonic fibroblasts) are plated at 10 cells per well. 4 The cells were inoculated in a 96-well plate at a density of 100 cells / well, and fresh culture medium containing the leachate of the coating material obtained in Example 1, Example 5, and Example 6 was added (the volume ratio of the leachate to the fresh culture medium was 1:9). Fresh culture medium was used as a negative control (Control), and 5 parallel groups were set for each material. After 24 h of culture, the cells were washed with PBS, CCK-8 reagent was added in the dark, and the cells were cultured in an incubator for 30 min. The absorbance at 450 nm was measured by an enzyme marker to calculate the cell survival rate. Figure 3 As shown, the cell survival rate of all materials tested in this experiment was always higher than 90%, which indicates that each group of materials in this study has good biosafety.

[0069] Example 10 In order to explore and evaluate the anti-bacterial adhesion performance of each material in the preparation process of PDA@PR@SBMA, Escherichia coli ( E. coli ) (Escherichia coli ATCC25922 from Southern Medical University, Guangzhou, China) was used as the test strain. The three coating materials obtained in Example 1, Example 5, and Example 6 were placed in a 96-well plate, and a blank group (blank silicone rubber sheet, Uncoated) was set up. 200 μL of bacterial solution (the concentration of the bacterial solution was 1×10 8 CFU / mL), and placed in a shaker for co-culture for 24 h. Separate the coating material from the bacterial solution, place the coating material in LB medium, take 100 μL of the gradient diluted LB medium and evenly spread it on a sterile LB agar plate, culture overnight, and observe the bacterial growth on the agar medium of each group of materials. Figure 4 As shown in the figure, the number of E. coli colonies on the silicone rubber sheet with PDA@PR@SBMA coating is the least, significantly less than other control groups. This is because in the presence of polyrotaxane structure, the zwitterions on the surface show flexible mobility, and the physical anti-biological adhesion performance is greatly improved, resulting in less bacterial colonization. This shows that PDA@PR@SBMA has good anti-bacterial adhesion properties.

[0070] Embodiment 11 In order to explore and evaluate the antibacterial biofilm adhesion performance of PDA@PR@SBMA in vitro, the morphology of biofilm adhesion on the surface of the material was observed by SEM. The coating materials obtained in Example 1, Example 5, and Example 6 were placed in a 96-well plate. E. coli (Escherichia coli ATCC25922 was obtained from Southern Medical University, Guangzhou, China) (The concentration of the bacterial solution was 1×10 8 After 48 h of co-culture with 100 μL of 500 μg / mL (CFU / mL), a biofilm was formed. The culture medium was discarded and 200 μL of electron microscopy fixative was added to each well for 4 h. The electron microscopy fixative was discarded and dehydrated with gradient concentrations of ethanol (50, 60, 70, 80, 100%) for 15 min. The dehydrated and dried samples were treated with sputtering gold on the surface. The treated materials were placed on a San EM bracket and the morphology was observed using SEM. The experimental results are shown in the figure. Figure 5 As shown in the scanning electron microscope image magnified 4000 times, the biofilm morphology formed by bacteria in the PDA coating group can be clearly observed. E. coli The colonies were densely packed to form a network biofilm structure. However, the number of biofilms on the surface of the control group PDA@SBMA coated with zwitterionic SBMA was significantly reduced, and only a few single bacteria were observed attached to the surface of the PDA@PR@SBMA material, which intuitively demonstrated the excellent anti-biofilm formation performance of the PDA@PR@SBMA coating material and proved that PDA@PR@SBMA has excellent anti-bacterial biofilm adhesion performance.

[0071] Example 12 In order to explore and evaluate the in vitro anti-protein adhesion performance of PDA@PR@SBMA, the experiment was divided into three groups: the three coating materials obtained in Example 1, Example 5, and Example 6. 2 μL 1 mg / mL BSA-FITC and 48 μL PBS solution were added to each group, and the materials were co-cultured in the dark at room temperature for 24 h. The materials and protein suspension were separated and washed three times with PBS to remove loose unadhered proteins on the surface of the materials. The protein adhesion on the surface of the materials was observed and photographed using a fluorescence microscope. Figure 6 As shown in the figure, in the process of PDA, PDA@SBMA, PDA@PR@SBMA and BSA-FITC acting together, a certain amount of protein adhesion will be shown. However, compared with the pure PDA coating group, the surface-modified SBMA coating PDA@SBMA has less protein fluorescence on the material surface, that is, the amount of protein adhesion has a significant decreasing trend. Similarly, in the same period of time, only a very small amount of protein is attached to the surface of the PDA@PR@SBMA coating with a polyrotaxane structure, proving that the coating material has good anti-protein adhesion properties. In the process of contact with proteins, effective anti-adhesion can inhibit the formation of biofilms, thereby providing a good basis for the prevention and treatment of biological infections and complications caused by retained silicone rubber implants in clinical practice.

[0072] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure, characterized in that: The method comprises the following steps: assembling a plurality of main molecules α-cyclodextrin and guest molecules double-terminated amino polyethylene glycol NH2-PEG-NH2 to form a pseudo-polyrotaxane PPR, and capping the polydopamine PDA coating to obtain a polyrotaxane PR structure with molecular mobility; and further modifying the coating surface with zwitterionic betaine to prepare a highly efficient anti-bioadhesion silicone rubber coating with a dynamic surface structure.

2. The preparation method according to claim 1, characterized in that: The specific steps include: (1) Synthesis of pseudopolyrotaxane PPR Take double-terminal amino polyethylene glycol NH2-PEG-NH2 and dissolve it in pure water, add a certain amount of α-cyclodextrin, and stabilize it with ultrasound until it becomes a uniform milky white colloid, and continue to stir at room temperature; the product is washed by centrifugation with pure water and freeze-dried to obtain pseudopolyrotaxane PPR; (2) Synthesis of polyrotaxane coating PDA@PR The pseudopolyrotaxane PPR obtained in step (1) is modified onto a polydopamine silicone rubber sheet to obtain a polyrotaxane coating PDA@PR; the polydopamine silicone rubber sheet is a silicone rubber sheet coated with a PDA coating; (3) Synthesis of zwitterion-modified polyrotaxane coatings The polyrotaxane coating PDA@PR obtained in step (2) is modified with zwitterionic betaine to obtain a zwitterionic modified polyrotaxane coating, i.e., a silicone rubber coating with a dynamic surface structure and high efficiency in resisting bioadhesion.

3. The preparation method according to claim 2, characterized in that: In step (1), The mass ratio of the double-terminated amino polyethylene glycol NH2-PEG-NH2 to α-cyclodextrin is 1:1-3; the amount of the double-terminated amino polyethylene glycol NH2-PEG-NH2 is calculated by adding 1-2 g per 10 mL of pure water; The molecular weight of the polyethylene glycol in the double-terminated amino polyethylene glycol NH2-PEG-NH2 is 3000 to 12000; The ultrasonic stabilization time is 5 to 15 minutes; the ultrasonic power is 200 to 700 W; The stirring time is 6 to 18 hours; The number of centrifugal washing is 3 to 4 times; The rotation speed of the centrifugal washing is 4000-8000 rpm, and the centrifugal time for each time is 20-50 min; In step (3), the zwitterionic betaine is methyl methacryloylethyl sulfobetaine SBMA.

4. The preparation method according to claim 2, characterized in that: The step (2) specifically comprises the following steps: soaking the polydopamine silicone rubber sheet in a Tris-HCl buffer, adding the pseudopolyrotaxane PPR obtained in the step (1), and stirring the reaction under normal temperature and pressure to obtain the polyrotaxane coating PDA@PR; The step (3) specifically comprises the following steps: placing the polyrotaxane coating PDA@PR obtained in step (2) in anhydrous N,N-dimethylformamide, then adding N,N′-carbonyldiimidazole, reacting, washing with anhydrous N,N-dimethylformamide, then placing in anhydrous N,N-dimethylformamide, then adding dibutylene glycol, continuing the reaction, and alternately washing the silicone rubber sheet with N,N-dimethylformamide and pure water to obtain a modified silicone rubber sheet; placing the modified silicone rubber sheet in anhydrous methanol solution of zwitterionic betaine, and continuing the reaction to obtain a zwitterionic modified polyrotaxane coating, that is, a silicone rubber coating with a dynamic surface structure and high efficiency and anti-bioadhesion.

5. The preparation method according to claim 4, characterized in that: In the step (2), The molar concentration of the Tris-HCl buffer is 1 to 3 M; The amount of the pseudopolyrotaxane PPR is 10-20 mg per 10 mL Tris-HCl buffer; the amount of the Tris-HCl buffer is per 25π mm 3 The silicone rubber sheet is calculated using 4 to 8 mL; The stirring reaction time is 12 to 36 hours; In the step (3), The amount of N,N′-carbonyldiimidazole is calculated by adding 50 to 200 mg per 5 mL of anhydrous N,N-dimethylformamide; the amount of anhydrous N,N-dimethylformamide is calculated by adding 50 to 200 mg per 25π mm 3 The amount of silicone rubber sheet is calculated by adding 5 to 15 mL; the amount of diaminodiphenylamine is calculated by adding 100 to 400 mg per 5 mL of anhydrous N,N-dimethylformamide; the amount of zwitterionic betaine is calculated by adding 0.5 to 2.5 g per 10 mL of anhydrous methanol; the amount of anhydrous methanol is calculated by adding 0.5 to 2.5 g per 25π mm 3 The silicone rubber sheet is calculated using 5 to 15 mL; The reaction time is 3 to 12 hours; The continued reaction time is 6 to 18 hours; The duration of the sustained reaction is 24 to 48 hours.

6. The preparation method according to claim 2, characterized in that: In step (1), the preparation method of the double-terminated amino polyethylene glycol NH2-PEG-NH2 comprises the following steps: dissolving polyethylene glycol PEG in anhydrous N,N-dimethylformamide, adding N,N′-carbonyldiimidazole and triethylamine, reacting at room temperature to obtain a mixed solution; dissolving ethylenediamine in anhydrous N,N-dimethylformamide, adding triethylamine, and then slowly adding the above mixed solution; reacting at room temperature, quenching the reaction, extracting the obtained product, and finally removing water, rotary evaporating to obtain the product double-terminated amino polyethylene glycol NH2-PEG-NH2; In step (2), the method for preparing the polydopamine silicone rubber sheet comprises the following steps: treating the surface of the silicone rubber sheet, then immersing it in anhydrous ethanol and ultrasonically treating it; after drying, immersing it in a Tris-HCl buffer solution containing dopamine hydrochloride, reacting it, washing it and drying it to obtain a silicone rubber sheet wrapped with a PDA coating, namely, a polydopamine silicone rubber sheet.

7. The preparation method according to claim 6, characterized in that: In step (1), The mass ratio of the N,N′-carbonyldiimidazole, polyethylene glycol PEG and ethylenediamine is 1:2-4:2-4; the amount of the triethylamine is 30-70 μL added to every 10 mL of anhydrous N,N-dimethylformamide; the amount of the polyethylene glycol PEG is 1-3 g added to every 10 mL of anhydrous N,N-dimethylformamide; The room temperature reaction time is 1 to 5 h; The time of slow addition is 1 to 5 h; The normal temperature reaction time is 12 to 15 hours; In step (2), The molar concentration of the Tris-HCl buffer is 5 to 10 mM; the amount of dopamine hydrochloride is calculated by adding 0.1 to 0.2 g per 10 mL Tris-HCl buffer; the amount of anhydrous ethanol and Tris-HCl buffer is calculated by adding 0.1 to 0.2 g per 25 π mm 3 The silicone rubber sheet is calculated using 4 to 8 mL; The surface treatment of the silicone rubber sheet is to treat the surface of the silicone rubber sheet with a plasma cleaning agent under normal pressure; The surface treatment time is 1 to 5 min; The ultrasonic treatment time is 1 to 3 hours; the ultrasonic power is 200 to 700 W; The reaction is carried out at 60 to 80° C. for 6 to 18 hours.

8. A highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7.

9. The use of the highly efficient anti-biological adhesion silicone rubber coating with a dynamic surface structure as claimed in claim 8, characterized in that: One of the following applications: (a) Application in high-efficiency anti-biological adhesion; (b) Application in the field of biomedical engineering; (c) Application in the preparation of retention silicone rubber implants.

10. The use according to claim 9, characterized in that: The anti-biological adhesion comprises at least one of anti-bacterial adhesion, anti-bacterial biofilm adhesion and anti-protein adhesion; further, the bacteria comprises Escherichia coli.